Challenges and Gender Disparities Faced by Women in Surgery in Pakistan - Akhtar, Ahmad; Gillani , Mushaim; Shariff , Yumna; Amna Inayat; Bahrawar, Manahil (International Journal of Medical Students, 2025)
Medicine continues to face significant challenges in gender imbalance. The issue of gender discrepancy in the field of surgery has become more pronounced in low or middle-income countries like Pakistan due to the growing trend of women leaving the healthcare profession after completing education. Even fewer graduates go on to become surgeons. Female surgeons face clinical biases, excessive workloads and lack of recognition. Cultural norms and patriarchal mindsets impose additional challenges, making it difficult for female surgeons to balance professional and personal responsibilities, particularly motherhood. Gender biases in hiring, salary disparities, and a lack of institutional support further exacerbate the issue. Deeply ingrained preferences for male surgeons, with workplace harassment, reinforce the gender gap in operating theaters. This leads to stress, burnout, and lower job satisfaction causing fewer females to opt for surgical fields, creating gender disparity. In recent years, a newer trend has emerged with more females following their passion, but there is an increased need for support groups, proper mentorship programs, and implementation of equal opportunities for both males and females. It requires mentorship, institutional reforms promoting inclusive hiring, flexible work policies, and cultural shifts to challenge gender norms. Encouraging representation in surgical networks and advocacy groups fosters an inclusive and diverse surgical workforce.